Multi-color luminescence evolution of La2Zr3(MoO4)(9): Ln(3+) (Ln(3+) = Dy3+ and/or Eu3+) nanocrystalline phosphors for UV-pumped white light-emitting devices - Feng, Jingchun; Xie, Weijie; Liu, Xiaoming; Tang, Xinghua; Yan, Liushui; Guo, Huiqin; Al Kheraif, Abdulaziz A.; Jang, Ho Seong; Lin, Jun (ELSEVIER, 2018)
Here, we demonstrate a new recreating blue-purple luminescence of La2Zr3(MoO4)(9) and host sensitized luminescence in La2Zr3(MoO4)(9): Ln(3+) (Ln(3+) = Dy3+ and/or Eu3+) nanocrystalline phosphors with multi-color luminescence evolution in response to UV light excitation. A series of La2Zr3(MoO4)(9) and La2Zr3(MoO4)(9): Ln(3+) (Ln(3+) = Dy3+ and/or Eu3+) nanocrystalline phosphors were synthesized via a citrate sol-gel method. X-ray diffractometer, FE-SEM, HRTEM, diffuse reflection spectra, photoluminescence spectra, and fluorescent decay lifetimes were utilized to characterize the prepared phosphors. The XRD results reveal that the prepared La2Zr3(MoO4)(9) and La2Zr3(MoO4)(9): Ln(3+) (Ln(3+) = Dy3+ and/or Eu3+) nanocrystalline phosphors present a single-phased trigonal crystal structure. FE-SEM and HRTEM images indicate that the prepared La2Zr3(MoO4)(9): Ln(3+) phosphors consist of fine and spherical grains in size of around 35-60 nm in diameter. Under the excitation of ultraviolet light, the La2Zr3(MoO4)(9) presents a characteristic broad band emission of MoO4 group from 300 to 550 nm peaking at 399 nm, and the La2Zr3(MoO4)(9): Ln(3+) (Ln(3+)= Dy3+ and/or Eu3+) phosphors show the characteristic emissions of Dy3+ (F-4(9/2) -> H-6(15/2) and F-4(9/2) -> H-6(13/2) transitions) and Eu3+ (D-5(0) -> F-7(J) transitions, J = 1, 2, 3, and 4), respectively. There exists an energy transfer from La2Zr3(MoO4)(9) host lattice to Dy3+ and Eu3+ ions in La2Zr3(MoO4)(9): Ln(3+) (Ln(3+) = Dy3+ and/or Eu3+) phosphor. The luminescence color of La2Zr3(MoO4)(9): Ln(3+) (Ln(3+) = Dy3+ and/or Eu3+) can be tuned from blue-white, white to orange-red by adjusting the doping concentration and the relative ratio of Dy3+ to Eu3+ in La2Zr3(MoO4)(9) host lattice. A single-phase white-light-luminescence with high color purity has been realized in La2Zr3(MoO4)(9): Dy3+, Eu3+ phosphor. The obtained La2Zr3(MoO4)(9): Dy3+, Eu3+ phosphor has potential application in area of UV-pumped white light-emitting devices.